1983
DOI: 10.1080/10862968309547475
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Details on the Recall of Major Ideas in Text

Abstract: Abstract. Four experiments were conducted to examine the effect of details on readers' recall of major ideas in text. With both artificial and natural texts, the presence of details enhanced recall of major idea units. Results are discussed in terms of an elaboration hypothesis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
2
0

Year Published

1984
1984
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 17 publications
3
2
0
Order By: Relevance
“…Subjects also recalled more idea units from major idea sentences supported by three related details and no unrelated details than from major idea sentences supported by one related detail and two unrelated details. These results are very similar to those reported by Phifer et al (1983) in which related details were simply deleted and not replaced by unrelated details.…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…Subjects also recalled more idea units from major idea sentences supported by three related details and no unrelated details than from major idea sentences supported by one related detail and two unrelated details. These results are very similar to those reported by Phifer et al (1983) in which related details were simply deleted and not replaced by unrelated details.…”
Section: Discussionsupporting
confidence: 81%
“…The current results suggest that as the number of unrelated details in a paragraph increase and as the number of related details in a paragraph decrease, it is more difficult for subjects to recall major ideas. The results are highly similar to those reported by Phifer et al (1983) in which the number of related details in paragraphs were varied without the inclusion of unrelated details. Even so, no clear effects of the number of related details, the number of unrelated details, or their combinations can be isolated from the results of Experiment 2.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…These scores increased from 44% at Level L to 96% at Level H: No other skill area experienced so large an increase. Such a result appears to support the claim that as the number of details supporting a major idea increases, so do the chances of recalling the major idea (Craik & Tulving, 1975; Phifer, McNickle, Ronning, & Glover, 1983). In other words, comprehension of details is thought by some to facilitate comprehension of major ideas on which inferential questions are focused.…”
Section: Discussionsupporting
confidence: 68%
“…Reder and Anderson (1980) found that reading summaries alone resulted in posttest performance as high as that obtained when entire chapters were read. Other studies, however, have found that the presence of details enhanced the recall of main ideas (Phifer, McNickle, Ronning, & Glover, 1983). Britton et al (1980) found that low-content information was remembered as well as high-content information (even though it was missing from recall protocols); it simply was not as easily retrieved from memory.…”
Section: Organizing a Text For Maximum Recallabilitymentioning
confidence: 99%